Between COVID-19, Coup, and Conflict: Multi-dimensional Threats to Human Security in Myanmar - Sabhita Kusuma, Ayusia (KnE Social Sciences, 2023)
Conflict and civil wars are ongoing in Myanmar. Internal displaced persons of Rohingya are now more than one million people, according to United Nations. Even during the COVID-19 pandemic, the Myanmar government continue using military approaches against its people, especially after the coup. This article will elaborates on the condition of Myanmar during the COVID-19 pandemic amid conflicts and military coups. It is essential to see how these three phenomena represent a multi-dimensional threat to the security of the people in Myanmar. This article uses a qualitative method with literature review as a data collection technique. Perspective of human security is used to analyse the issues regarding conflict, COVID-19, and coup in Myanmar with several dimensions of approach. The findings of this article show that the COVID-19 pandemic has further exacerbated the human security for the people of Myanmar during conditions of conflict and continuous repression from the junta regime. Keywords: COVID-19, conflict, coup, military regime, human security